ChemInform Abstract: Diterpenoid Lanceolatins A—G from Cephalotaxus lanceolata and Their Antiinflammatory and Antitumor Activities. Issue 24 (June 2015) - He, Yi‐Ren; Shen, Yun‐Heng; Shan, Lei; Yang, Xi; Wen, Bo; Ye, Ji; Yuan, Xing; Li, Hui‐Liang; Xu, Xi‐Ke; Zhang, Wei‐Dong
Abstract: isolation, structure determination, antiinflammatory and antitumor activity of seven new diterpenoids, lanceolatins A—G (I)—(VI), along with five known diterpenoids